Adults' age-related differences in strategy perseveration are modulated by response-stimulus intervals and problem features. Issue 10 (October 2014) - Lemaire, Patrick; Brun, Fleur
Ageing results in the tendency of older adults to repeat the same strategy across consecutive problems more often than young adults, even when such strategy perseveration is not appropriate. Here, we examined how these age-related differences in strategy perseveration are modulated by response-stimulus intervals and problem characteristics. We asked participants to select the best strategy while accomplishing a computational estimation task (i.e., provide approximate sums to two-digit addition problems like 38 + 74). We found that participants repeated the same strategy across consecutive problems more often when the duration between their response and next problem display was short (300 ms) than when it was long (1300 ms). We also found more strategy perseverations in older than in young adults under short Response-Stimulus Intervals, but not under long Response-Stimulus Intervals. Finally, age-related differences in strategy perseveration decreased when problem features helped participants to select the best strategy. These modulations of age-related differences in strategy perseveration by response-stimulus intervals and characteristics of target problems are important for furthering our understanding of mechanisms underlying strategy perseveration and, more generally, ageing effects on strategy selection.